Multimedia as a Tool of Patriotic Education of Students - Hryhoriy Vasianovych (Vasyl Stefanyk Precarpathian National University, 2016)
The article analyzes the problem of patriotic education of students by means of multimedia in a class-room environment. The author pays the main attention to both the creation of didactic materials for social and human sciences and the use of the interactive whiteboard in the educational process. Using these means, it is important for teachers to define the theme and the purposes of a lesson, to carry out structural and block distribution of the material and to outline the dynamics of its presentations as well as to prepare recommendations for self-study, questions for control and self-control etc. It is stressed that the principle of training interactivity is an important means of patriotic education of students.